Development of herbal syrup from ginger (zingiberofficinale), lemongrass (cymbopogoncitratus), seaweed (kappaphycusstriatum), and beetroot (betavulgarisl.) - Mansoor Abdul Hamid; Han Fei Loh; Sugiyanto; Moh. Mahfud Effendi; Akhsanul In`am (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The traditional method of herbal syrup production is by simmering a mixture of sliced herbs for several hours before undergoing a straining process to utilize the liquid parts. The usage of fresh herbs and this simmering process made the product inconsistent in quality. Therefore, in this study, ginger and lemongrass have been used in powder form, and seaweed, and beetroot were added to study they effects on the quality of the herbal syrup. Nine formulations of herbal syrup were developed, where all the formulations set with a fixed amount of ginger and lemongrass powder at 2.4% and 1.0%, respectively. The percentage of seaweed and beetroot used ranged from 1.5% to 2.5% and 0.5% to 1.5%, respectively. The best formulation was selected based on ranking and hedonic of sensory evaluation, as well as its physicochemical properties. Results showed that formulation 3, which consisted of 2.4% ginger, 1.0% lemongrass, 1.5% seaweed, and 1.5% beetroot, was chosen as the best formulation with a brighter color, significantly higher (p<0.05) total soluble solid (49.70±0.06 brix), and viscosity (1143.33±1.15 cp) due to the addition of seaweed. Furthermore, the F3 sample also took significantly longer (p<0.05) (80 min) to show sedimentation. Proximate values of F3 were significantly higher (p<0.05) in ash (3.36±0.22%), protein (0.39±0.02%), and crude fiber (6.22±0.11%), but lower in carbohydrates (46.22±0.25%). F3 has showed a significantly higher (p<0.05) in antioxidant activity on DPPH scavenging power compared to control with 85.73±0.96 and 51.19±0.89 respectively.